Diurnal Rhythmicity in the Transcription of Jejunal Drug Transporters† - Adam T. Stearns; Anita Balakrishnan; David B. Rhoads; Stanley W. Ashley; Ali Tavakkolizadeh (Elsevier, 2008)
Intestinal drug efflux proteins play a major role in the pharmacokinetics of many drugs. We assessed diurnal rhythmicity in the expression of ten major drug transporters. We acquired male Sprague-Dawley rats and harvested jejunal mucosa at 3-h intervals across a 24-h period. qPCR was performed for ten transporters: Mdr1, Mdr3, Mrp1 - 3, Mct1, Brcp, Pept1, Octn2, and Oatp-b. Rhythmicity was assessed with the cosinor procedure. Diurnal rhythmicity was observed for Mdr1, Mct1, Mrp2, Pept1, and Bcrp (1.6 - 5.4-fold-changes). Acrophases occurred during fasting hours. We conclude that many drug transporters display profound diurnal rhythms in transcription, which may underlie diurnal rhythms in drug pharmacokinetics. Keywords:: diurnal rhythm, intestinal, drug efflux transporter